Belief formation in a signalling game without common prior: An experiment - Alex Possajennikov (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
Using belief elicitation, the paper investigates the formation and the evolution of beliefs in a signalling game in which a common prior on Sender's type is not induced. Beliefs are elicited about the type of the Sender and about the strategies of the players. The experimental subjects often start with diffuse uniform beliefs and update them in view of observations. However, the speed of updating is influenced by the strength of the initial beliefs. An interesting result is that beliefs about strategies are updated faster than beliefs about types. In the medium run, for some specifications of game parameters, this leads to outcomes being significantly different from the outcomes of the game in which a common prior is induced. It is also shown that elicitation of beliefs does not considerably change the pattern of play.
Keywords: C91; D83; C72; 330; beliefs; signalling; experiment; learning; belief elicitation